Impact of Intrinsic and Extrinsic Factors on Employee Performance in Nepalese Organizations - Rajaure, Samrat (Nepalese Journal of Economics, 2025)
This study examines the impact of intrinsic and extrinsic factors on employee performance in Nepalese organizations. Employee performance is the dependent variable. The selected independent variables are bonus, recognition, promotion, salary empowerment and career growth opportunities. The primary source of data is used to assess the opinions of the respondents regarding the impact of extrinsic and intrinsic factors on employee performance. This study is based on primary data with 121 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of intrinsic and extrinsic factors on employee performance in Nepalese organizations. The study showed that salary has a positive impact on employee performance. It means that increase in salary leads to increase in employee performance. Similarly, bonus has a positive impact on employee performance. It indicates that increase in bonus leads to increase in consumer employee performance. Moreover, recognition has a positive impact on employee performance. It means that increase in recognition leads to increase in employee performance. Likewise, empowerment has a positive impact on employee performance. It shows that increase in empowerment leads to increase in employee performance. Similarly, career growth opportunities have positive impact on employee performance. It shows that better the career growth opportunities, higher would-be the employee performance. Further, promotion has a positive impact on employee performance. It shows that higher the promotion, higher would be the employee performance.